Magnetic properties of coordination clusters with Mn4 and Co4 antiferromagnetic cores. Issue 6 (27th January 2022) - Achilli, Simona; Besson, Claire; He, Xu; Ordejón, Pablo; Meyer, Carola; Zanolli, Zeila
Abstract : Tailoring magnetic properties of antiferromagnetic coordination clusters by changing the inner core. Abstract : We present a joint experimental and theoretical characterization of the magnetic properties of coordination clusters with an antiferromagnetic core of four magnetic ions. Two different compounds are analyzed, with Co and Mn ions in the core. While both molecules are antiferromagnetic, they display different sensitivities to external magnetic field, according to the different atomic magnetic moments and strength of the intra-molecular magnetic couplings. In particular, the dependence of the magnetization versus field of the two molecules switches with temperature: at low temperature the magnetization is smaller in Mn4 than in Co4, while the opposite happens at high temperature. Through a detailed analysis of the electronic and magnetic properties of the two compounds we identify a stronger magnetic interaction between the magnetic ions in Mn4 with respect to Co4 . Moreover Co4 displays not negligible spin–orbit related effects that could affect the spin lifetime in future antiferromagnetic spintronic applications. We highlight the necessity to account for these spin–orbit effects together with electronic correlation effects for a reliable description of these compounds.